RAPID DETERMINATION OF CRUCIAL PARAMETERS FOR THE OPTIMIZATION OF MILLING PROCESS BY USING VISIBLE/NEAR INFRARED SPECTROSCOPY ON INTACT OLIVES AND OLIVE PASTE - Giovenzana, V.; Beghi, R.; Civelli, R.; Trapani, S.; Migliorini, M.; Cini, E.; Zanoni, B.; Guidetti, R. (Italian Journal of Food Science, 2017)
The aim of this work is the application of vis/NIR spectroscopy in order to correlate spectral data acquired on intact olives just before or in pastes during the milling process, to the crucial parameters for the optimization of the process. Physical measurements (i.e. yield point force and total deformation energy) were performed on the olive samples; after the fruit were crushed for olive paste production, chemical analysis (moisture, oil and sugars content) and maturity index (MI) were measured and correlated to the spectral data. The obtained results were encouraging for chemical, texture and MI parameters, demonstrating the feasibility of real-time prediction of important indices for the milling plant settings.